Clinicopathological assessment of chronic hyperplastic candidasis - Hussain, Hussain S; Al-Drobie, Ban F (Journal of Baghdad College of Dentistry, 2022)
Background: Chronic hyperplastic candidiasis is the least common type of oral candidiasis. The diagnosis, long-term treatment, and prognosis of this potentially malignant oral condition are still currently unclear. Objective: the aim of this study is to analyze the demographic features and clinical characteristics of oral chronic hyperplastic candidiasis. Materials and Methods: A retrospective analysis was performed on blocks and case sheets of patients who were diagnosed with chronic hyperplastic candidiasis in the archives of Oral and Maxillofacial Pathology at the College of Dentistry/University of Baghdad. Demographic and clinical characteristics were analyzed. Results: twenty-one cases with chronic hyperplastic candidiasis were collected and reviewed. Buccal mucosa was the most affected sites. Regarding the clinical features, lesions color frequently presented as white plaque. Regarding clinical diagnosis, leukoplakia was noted the highest one among other previous diagnosis. Conclusions: Older adults are the mostly affected age group by chronic hyperplastic candidiasis with slight male predilection. White plaque is the most presented clinical feature with buccal mucosa being the most affected oral site.